Determination of Catalyst Surface Acidity in Liquids by a Pulse Liquid Chromatographic Technique - Paolo Carniti; Antonella Gervasini; Serena Biella (Adsorption Science & Technology)
A pulse liquid chromatographic technique, set up by using an HPLC apparatus, is proposed for the characterization of the surface acidity of solid acids in liquids in view of their use as catalysts in liquid–solid reactions. Dosed amounts of solutions of two different basic probe molecules (2-phenylethylamine, pK a = 9.84 and aniline, pK a = 4.63) in solvents of different polarity were injected onto solid samples (acidic resins, Amberlites and a mixed silica–zirconia oxide) at a constant solvent flow rate. Titration with the weakest basic probe (aniline) rather than 2-phenylethylamine generally led to a lower amount of acidic sites. The amount of acidic sites determined at the surface was greatly affected by the solvent. With silica–zirconia, a higher amount of acidic sites was established by titration in apolar rather than polar solvents. The results have been compared with those obtained by conventional methods, i.e. ion exchange employing salts and, for silica–zirconia, Hammett titrations. The quite satisfactory results obtained are of some importance in establishing valuable relationships between catalyst acidity and catalytic activity in various solvents.